Reconocimiento de primitivas 3D, usando autocorrelación y ANFIS - Guerra Monterroza, Emil Javier (Visión electrónica, 2010)
The present work shows a metodology for reconition and clasification of four (4), primitive three-dimensional such as: cylinder, cube, sphere and cone, which are contained in images of 128X128 pixels. The methodology is based on the application of autocorrelation algoritm, for the extraction of charcteristics in images, and he classification process is made by means of ANFIS, that is a hybrid between the artificial neuronal networks and the fuzzy logic. In the phase of operation, the system must be able to differentiate the primitive ones mentioned, in an independent way of the angle of acquisition of the image. The described system, for example, can be connected to a robotic arm stops to perfom tasks of classification of objects according to its form.